Evaluation of panoramic radiomorphometric indices in Indian population - Sumona Pal; Sunita Amrutesh (Cumhuriyet University, 2013)
Objecitves: Radiomorphometric indices on dental radiographs can be used for screening of osteoporosis. However population-specific normative data is sparse. Aim was to establish radiomorphometric indices in Indian population and to determine role of age, gender and dentition on these indices. Materials and Methods: Cross sectional study was undertaken from January 2010 to December 2010. OPGs of 80 samples were divided into four age groups. Mental index, panoramic mandibular index, mandibular cortical index, antegonial index were measured. Relationships with age and dentition were analysed using Statistical Package for the Social Sciences SPSS12.0. Student t-test, one way analysis of variance, Chi square test was used to find the statistical significance. P value < 0.05 was considered to be significant. Results: In most of the study population endosteal margins of the mandibular cortex were even and sharp on both sides i.e.C1 appearance except in 60-69 years females who showed increased tendency of lacunar cortical defects i.e. C2 appearance. No correlation between dentition and mandibular cortical index (MCI), mental index (MI), panoramic mandibular index (PMI) & Antegonial index (AI) (p value 0.583, 0.059, 0.491 respectively). Population's mean of AI, MI, and PMI among males were 3.33, 3.97, 0.33 respectively and among females were 3.06, 3.64, and 0.32 respectively. (p value for AI, MI, PMI were 0.048, 0.028,0.037 respectively). Conclusions: All indices negatively correlated with age. There was a general downward trend with age until sixth decade, when values declined sharply. No statistical significance was found between AI, MI, and PMI and dentition.